2020
DOI: 10.1371/journal.pone.0234977
|View full text |Cite
|
Sign up to set email alerts
|

Prediction modelling studies for medical usage rates in mass gatherings: A systematic review

Abstract: Background Mass gathering manifestations attended by large crowds are an increasingly common feature of society. In parallel, an increased number of studies have been conducted that developed and/or validated a model to predict medical usage rates at these manifestations. Aims To conduct a systematic review to screen, analyse and critically appraise those studies that developed or validated a multivariable statistical model to predict medical usage rates at mass gatherings. To identify those biomedical, psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…This is in line with results of a recent study that used multivariable regression trees for prediction of PPR at a wide variety of more than 200 MGs in Australia [ 24 ]. In a recent systematic review [ 10 ], we found that MG category was significantly associated with PPR in 5 out of 6 studies that included MG category as a predictor variable for PPR [ 2 , 5 , 20 , 24 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is in line with results of a recent study that used multivariable regression trees for prediction of PPR at a wide variety of more than 200 MGs in Australia [ 24 ]. In a recent systematic review [ 10 ], we found that MG category was significantly associated with PPR in 5 out of 6 studies that included MG category as a predictor variable for PPR [ 2 , 5 , 20 , 24 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our systematic review [ 10 ], we found that temperature (including heat index, a combined measure of air temperature and relative humidity) was positively associated with PPR in 5 out of 7 papers that evaluated ambient temperature at outdoor events [ 2 , 5 , 22 , 24 27 ]. This relationship is confirmed by our current analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial certainty level of the included prediction modelling studies was set at 'high' because the association between the predictors and outcomes was considered irrespective of any causal connection. 39 The overall certainty level was, however, downgraded to 'moderate' and then 'low' because of inconsistent results (high heterogeneity) and the large proportion of high overall risk of bias amongst studies. The final overall certainty of 'low' implies that our confidence in the effect estimates is limited and further research is very likely to change the effect estimate.…”
Section: Certainty Of Evidencementioning
confidence: 99%